PENGARUH KUALITAS KEHIDUPAN KERJA DAN STRES KERJA TERHADAP KEPUASAN KERJA DAN DISIPLIN KERJA PADA PT. INFOMEDIA NUSANTARA DI SURABAYA - Isti Soleharti; Djawoto Djawoto; Suhermin Suhermin (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This study dicusses the direct influence of quality of work life and work stress on job satisfaction and work discipline and the indirect effect of quality of work life on work discipline through job satisfaction as an intermediate variable and the indirect effect of work stress on work discipline through job satisfaction as a variable between . This research uses path analysis, F test, t test and sobel test. The sampling technique in this research is non-probability sampling of 135 respondents. The results of this study indicate that the quality of work life has a positive and significant effect on work discipline, work stress has a negative and significant effect on work discipline. The quality of work life has a positive and significant effect on job satisfaction, work stress has a negative and significant effect on job satisfaction, job satisfaction has a positive effect. and significant work discipline. In addition there is an indirect effect between quality of work life on work discipline through job satisfaction and there is an indirect effect between work stress on work discipline through job satisfaction.